Endogenous Elevation of Homocysteine Induces Retinal Neuron Death in the Cystathionine-β-Synthase Mutant Mouse - Ganapathy, Preethi S. (2009)
PURPOSE: To determine the effects of endogenous elevation of homocysteine on the retina using the cystathionine β-synthase (cbs) mutant mouse. METHODS: Retinal homocysteine in cbs mutant mice was measured by high-performance liquid chromatography (HPLC). Retinal cryosections from cbs(−/−) mice and cbs(+/−) mice were examined for histologic changes by light and electron microscopy. Morphometric analysis was performed on retinas of cbs(+/−) mice maintained on a high-methionine diet (cbs(+/−) HM). Changes in retinal gene expression were screened by microarray. RESULTS: HPLC analysis revealed an approximate twofold elevation in retinal homocysteine in cbs(+/−) mice and an approximate sevenfold elevation in cbs(−/−) mice. Distinct alterations in the ganglion, inner plexiform, inner nuclear, and epithelial layers were observed in retinas of cbs(−/−) and 1-year-old cbs(+/−) mice. Retinas of cbs(+/−) HM mice demonstrated an approximate 20% decrease in cells of the ganglion cell layer (GCL), which occurred as early as 5-weeks after onset of the HM diet. Microarray analysis revealed alterations in expression of several genes, including increased expression of Aven, Egr1, and Bat3 in retinas of cbs(+/−) HM mice. CONCLUSIONS: This study provides the first analysis of morphologic and molecular effects of endogenous elevations of retinal homocysteine in an in vivo model. Increased retinal homocysteine alters inner and outer retinal layers in cbs homozygous mice and older cbs heterozygous mice, and it primarily affects the cells of the GCL in younger heterozygous mice. Elevated retinal homocysteine alters expression of genes involved in endoplasmic reticular stress, N-methyl-D-aspartate (NMDA) receptor activation, cell cycle, and apoptosis.